Pengaruh Produksi, Harga Bawang Merah, Inovasi Teknologi Pertanian dan Kelembagaan Terhadap Keberlajutan Usahatani di Kabupaten Brebes - subagio, subagio; Lilis Siti Badriah; Abdul Aziz Ahmad (Jurnal Ilmiah Ekonomi Global Masa Kini, 2023)
Fluctuations in shallot prices, harvested area, and shallot production that accurredin Brebes district have had an impact on reducing the sustainabilityof shallot farming. Farming sustainability is ability to remain productive while maintaining or improving quality of environment and conserving natural resources. Factors that effect shallot farming sustainability include production, price, farming technological innovation, and farming institutions. The purpose of this study was to analyze the effect of production, price, farming technological innovation and institutions on shallot farming sustainability. This research method used survey research with a quantitative approach. The research population was shallot farmers in three shallot center locations in Brebes Regency, namely Brebes District, Wanasari District, and Larangan District, with a total of 62,505 people. The sampling technique used cluster sampling, stratified random sampling, and Taro Yamane formula for a total of 100 people. The data collection technique used a questionnaire which was analyzed through regression analysis. The results showed that production had a significant effect on shallot farming sustainability, price had a significant effect on shallot farming sustainability, farming technological innovation had a significant effect on shallot farming sustainability, and institutions had a significant effect on shallot farming sustainability. Production, prices, farming technological innovation, and institutions were able to had a simultaneous effect on farming sustainability by 36.2%. The implication for shallot farming actors must be able to maintain production quality, shallot prices, keep abreast of new agricultural technology developments and always acsess agricultural information from extension workers so that their farming operations can be sustainable.   Keywords: Production, Price, Technological, Institutional, Sustainability.